PLUGIN UTILIZATION GOOGLE FORMS AUTOPROCTOR FOR ASSESSMENT OF STUDENT LEARNING OUTCOMES - Mudopar; Riri Mukhariroh (Cirebon International Conference on Education and Economics Proceeding, 2024)
Competence in the use of information technology in the learning process and learning evaluation which is increasingly oriented towards technology can no longer be avoided. Evaluate student learning outcomes with a free multi-platform digital evaluation utilizing existing facilities including Google Form. This application can be used to carry out assessments such as quizzes and collect responses.However, in practice there is a lot of fraud in the assessment or evaluation process. This research was conducted to determine the effectiveness of utilizing the evaluation process for teaching and learning activities through online evaluation with the Google Form application and exam supervision through proctoring with the help of the Autoproctor Plugin. This research uses a descriptive qualitative approach, with data collection techniques in the form of tests and documentation. The subjects of this research involved students in class VIII K at SMPN 4 Cirebon City. The application of the Autoproctor plugin on Google Form has proven to be effective in the process of assessing student learning outcomes. Also, another advantage is that using the Autoproctor Plugin is free.